Evaluation of spectral domain and time domain optical coherence tomography findings in toxoplasmic retinochoroiditis - Bruno Diniz; Caio V. Regatieri; Rafael Andrade; Maia (2011)
To investigate spectral domain optical coherence tomography (SD-OCT) findings and compare them with time domain (TD)-OCT imaging of macula and retinochoroiditis lesions of patients with toxoplasmosis.Prospective cross-sectional study.Ten eyes of 10 patients with active toxoplasmic retinochoroiditis were included. Morphologic features from the macula and retinochoroiditis lesions were obtained at baseline and at 6-week follow up. Scan acquisition protocols for TD-OCT included raster and radial lines through the retinochoroiditis lesion, fast macular, and a linear scan from the lesion to the fovea, whereas the acquisition protocols for SD-OCT also included horizontal volume scans at the lesion site and at the macula. Thickness measurements obtained by SD-OCT were analyzed.At baseline, macular serous retinal detachment was observed in five patients; two of them only seen by SD-OCT. Retinochoroidal lesions were 4260 μm distant from the fovea on average (R = 681-7130) and this distance had an indirect correlation to the presence of macular detachment. Epiretinal membrane and vitreo-macular traction were also observed. The posterior hyaloid was not identified in four patients by TD-OCT and only in one by SD-OCT at baseline. Perilesional subretinal fluid was observed in two patients. The median retinal thickness significantly decreased at the retinochoroiditis lesion (P = 0.0004), and all the patients remained with disorganized retinal layers reflectivity at follow up.SD-OCT is a useful tool in the diagnosis of macular changes related with toxoplasmic retinochoroiditis. SD-OCT is superior in evaluating retinal changes associated with ocular toxoplasmosis.